(untitled) (Docentes 2.0 Journal, 2024)
Every scientific society formed by students from private universities should be a research promoter. The objective of the present study was to identify the characteristics and importance of research groups of students from private universities. The positivist paradigm, deductive method, quantitative approach, non-experimental design, descriptive type, and cross-sectional research methodology were used in this work. Electronic surveys were applied, and a non-probabilistic sample was used. Among the most relevant findings, we have that students consider the training processes in research-related topics to be primordial; they also express the importance of the publication of systematic articles by the student population. It is concluded that in La Paz, there are few or nonexistent scientific societies in the framework of private higher education, which are an opportunity to create professional and inter-institutional links that support knowledge management. It is advisable to finance initiatives that support students with easy and practical exploration processes so that they receive permanent guidance from research institutions.